2017
DOI: 10.1159/000464281
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss and Risk of Mild Cognitive Impairment and Dementia: Findings from the Singapore Longitudinal Ageing Study

Abstract: Aim: To investigate the associations between hearing loss and prevalent and incident mild cognitive impairment (MCI), dementia and MCI or dementia (all cases). Methods: Cross-sectional and longitudinal analyses of baseline and follow-up data were performed in a population-based cohort. The baseline sample of 2,599 adults aged ≥55 included 1,515 cognitively normal subjects who were followed up to 8 years. Hearing loss at baseline was determined by the whispered voice test, and MCI and dementia by Mini-Mental St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 31 publications
3
74
0
1
Order By: Relevance
“…Although still limited in number, these studies report consistent results, supporting the hypothesis of an increased risk of dementia which remains significant even after statistically accounting for potential confounders such as demographic and/or cardiovascular factors. Such results have been gathered from studies considering hearing loss either with audiometric measures [15,27,28], speech recognition tests [29], or indirect/self-reported measures [30][31][32]. Although most of the studies considered peripheral hearing loss, the link between age-related central auditory processing disorder [33] and cognitive decline and/or dementia has also been reported by two longitudinal studies [34,35].…”
Section: Hearing Loss and Age-related Cognitive Decline: Two Highly Fmentioning
confidence: 99%
“…Although still limited in number, these studies report consistent results, supporting the hypothesis of an increased risk of dementia which remains significant even after statistically accounting for potential confounders such as demographic and/or cardiovascular factors. Such results have been gathered from studies considering hearing loss either with audiometric measures [15,27,28], speech recognition tests [29], or indirect/self-reported measures [30][31][32]. Although most of the studies considered peripheral hearing loss, the link between age-related central auditory processing disorder [33] and cognitive decline and/or dementia has also been reported by two longitudinal studies [34,35].…”
Section: Hearing Loss and Age-related Cognitive Decline: Two Highly Fmentioning
confidence: 99%
“…For instance, several studies report a positive linkage between a pair of cerebrovascular disease, hearing loss and cognitive impairment, which is being affected by age, education, stroke history and vascular disorder (e.g. hypertension, diabetes) . This line of research also suffers from paying attention to only a small set of factors for the association (excluding social determinants, such as family support and social activity) and/or having a cross‐sectional research design (which cannot analyze a causal relationship between the association and its determinants).…”
Section: Introductionmentioning
confidence: 99%
“…hypertension, diabetes). [7][8][9][10][11][12] This line of research also suffers from paying attention to only a small set of factors for the association (excluding social determinants, such as family support and social activity) and/or having a cross-sectional research design (which cannot analyze a causal relationship between the association and its determinants). Indeed, new methods might be required for the prediction of the association as a set of multiple dependent variables, given that making a prediction over a set of multiple dependent variables is much less accurate and effective than doing so for a single dependent variable.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that deficits in cognitive function may transition to dementia, and mild cognitive impairment is now considered a risk factor for dementia [3]. Furthermore, cognitive impairment is associated with various age-related conditions [4,5,6]. Although multiple factors including oxidative stress and inflammation play a part in age-related cognitive decline [7,8], the precise mechanism underlying the decline in cognitive function remains unknown.…”
Section: Introductionmentioning
confidence: 99%